PENGARUH DEBT TO ASSET RATIO (DAR) DAN CURRENT RATIO (CR) TERHADAP RETURN ON EQUITY (ROE) PADA PT ACE HARDWARE INDONESIA TBK PERIODE 2011-2023 - Fitri Indriani; Hendri Gunawan (Journal of Research and Publication Innovation, 2025)
This research aims to determine the effect of Debt To Asset Ratio (DAR) and Current Ratio (CR) on Return On Equity (ROE) both partially and simultaneously at PT Ace Hardware Indonesia Tbk. The research method used is a quantitative method. The population in this research is all of the Financial Reports of PT Ace Hardware Indonesia Tbk. The sample used in this research is the financial position report and profit and loss report from 2011 – 2023. The data analysis techniques used are Descriptive Analysis, Classical Assumption Test, Coefficient of Determination Test, Multiple Linear Regression Analysis, and Hypothesis Testing. The results of this research show that the t value of Debt To Asset Ratio is -1.886 which is smaller than the t table value of 2.22814 (-1.886 < 2.22814) with a significance value of 0.089 which is greater than 0.05 (0.089 > 0.05). So it can be concluded that the Debt To Asset Ratio has no effect and is not significant on Return On Equity. Meanwhile, the t-calculated Current Ratio value of -2.562 is greater than the t-table value of 2.22814 (-2.562 > 2.22814) and the significant Current Ratio result of 0.028 is smaller than 0.05 (0.089 < 0.05). So it can be concluded that the Current Ratio has a negative and significant effect on Return On Equity. Debt To Asset Ratio and Current Ratio simultaneously have an influence and significance on Return On Equity at PT Ace Hardware Indonesia Tbk for the 2011-2023 period as evidenced by the Fcount of 4.843 which is greater than the Ftable of 3.98 (4.8443 > 3.9) and the value significant of (0.034 < 0.05).